Balkan family structure and the European pattern : demographic developments in Ottoman Bulgaria - Todorova, Marii͡a Nikolaeva (Budapest ; New York : Central European University Press, 2006)
This study, which is an updated, extended, and revised version of the out-of-print 1993 edition, reassesses the traditional stereotype of the place of the Balkans in the model of the European family in the nineteenth century on the basis of new source material and by synthesizing existing research. The work first analyzes family structure and demographic variables as they appear in population registers and other sources, and the impact of these findings on theoretical syntheses of the European family pattern. On most features, such as population structure, marriage and nuptiality, birth and fertility, death and mortality rates, family and household size and structure, as well as inheritance patterns, the Balkans show an enormous deal of internal variety. This variability is put in a comparative European context by matching the quantifiable results with comparable figures and patterns in other parts of Europe. The second section of the book is a contribution to the long-standing debate over the zadruga, the complex, collective, joint or extended family in the Balkans. Finally, the book considers ideology and mythology and the ways it has adversely affected scholarship on the family, and broadly on population history.
Introduction : rethinking the unknown -- Population structure -- Age structure -- Sex structure -- Marriage and nuptiality -- The marriage ritual and seasonal patterns of marriage -- Age at marriage -- Remarriage, cross-kin marriages and other characteristics -- Birth and fertility -- Births, baptisms and their registration -- Measurements of fertility -- Twins in a closed population -- Death and mortality -- Gender and age specific mortality -- Seasonal patterns of mortality and causes of death -- Family and household size and structure -- Family and household structure -- Family and household size -- Inheritance patterns -- The problem of the South Slav zadruga -- Distribution and development of the zadruga in the Balkans -- An alternative explanation -- Conclusion : a hypothesis of converging theories -- A summary of conclusions -- Appendices -- The sources -- The liber status animarum of the village of Seldzhikovo -- Ideographs of the liber status animarum -- Note on the plague -- A marriage contract -- On the epistemological value of family models : the Balkans within the European pattern.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Bulgaria -- Population; Family demography -- Bulgaria; Bulgaria -- Social life and customs; Démographie de la famille -- Bulgarie; SOCIAL SCIENCE -- Demography; HISTORY -- Europe -- Eastern; Family demography; Manners and customs; Population; Bulgaria; 19th century, Demography, Family life, Ottoman Empire, Population, Social life and customs